Art et nouvelles technologies : pour un recadrage de la subjectivité humaine par rapport à l’idée de paysage - Pageot, Édith-Anne (RACAR : Revue d'art canadienne / Canadian Art Review)

(untitled) (UAAC-AAUC (University Art Association of Canada | Association d'art des universités du Canada), 2010)
This article addresses the impact of new media on concepts of landscape. More precisely, it concerns artistic projects using new media that incorporate elements of nature. It shows how these projects participate in an economy of landscape, but at the same time reformulate the very principles associated with the genre. Four projects are presented as case studies: Glenlandia (2005–07) by Susan Collins, Osmose (1995) by Charlotte Davies, Tele-Garden (1995–2004) by Kenneth Goldberg and Joseph Santarromana, and One Tree(s) (1999–) by Natalie Jeremijenko. In essence, these projects deal not with ecology so much as with new spatio-temporal relations of the perceiving subject with nature, relations always mediated by the concept of landscape. As defined by “ecosophy,” these spatio-temporal relations are open to exploration and adaptation characterized by continuous change. These changes include distortion, movement, and a form of blindness that weaken the dominant position of vision in human perception of the world. The projects in question overturn the opposition between humanity and nature that had been, from the beginning of the modern era, the basis of landscape, a genre characterized by frontality, alterity, and pure opticality.